F ( x ) = x + x + x + . . . x x x x
If the value of the first derivative of F ( x ) at x = 1 can be expressed as c a b − b for integers a , b , and c , find the value of a + b + c .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice problem and solution. I took a slightly different approach.
I first differentiated (implicitly) the equation y 2 + x y − x = 0 to find that
2 y y ′ + y + x y ′ − 1 = 0 ⟹ y ′ ( x + 2 y ) = 1 − y ⟹ y ′ = x + 2 y 1 − y .
Now with y ( 1 ) = a we have that a = 1 + a 1 ⟹ a 2 + a − 1 = 0 ⟹ a = 2 − 1 + 5 ,
as clearly a > 0 . We then find that
y ′ ( 1 ) = x + 2 y ( 1 ) 1 − y ( 1 ) = 1 + ( − 1 + 5 ) 1 − 2 − 1 + 5 = 2 5 3 − 5 = 1 0 3 5 − 5 .
Why does it strictly have to be a + before the square root when you use the quadratic formula? Why can't a minus replace it?
Log in to reply
When we plug x = 1 into the expression for y the result will be a value between 0 and 1 . The only root that fits this description is the one with the + sign before the square root, as the other root will be < 0 .
Let, F ( x ) = x + x + x + . . . x x x x F ( x ) = x + F ( x ) x F ( x ) 2 + x F ( x ) − x = 0
by ignoring the negative value,
F ( x ) = 2 x 2 + 4 x − x F ′ ( x ) = 2 x 2 + 4 x x + 2 − x 2 + 4 x F ′ ( 1 ) = 2 5 3 − 5 = 2 5 5 3 5 − 5 5 = 1 0 3 5 − 5 ≡ c a b − b
therefore, a = 3 , b = 5 , c = 1 0 a + b + c = 3 + 5 + 1 0 = 1 8
Problem Loading...
Note Loading...
Set Loading...
F ( 1 ) = 1 0 3 5 − 5